MITOS NYAI RORO KIDUL DALAM NOVEL SANG NYAI - Suci Andari; Safrina Noorman; Teddi Muhtadin (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2016)
This writing titled "Mitos Nyai Roro Kidul dalam Novel Sang Nyai". The data is a mythical story of Nyai Roro Kidul on the Sang Nyai novel as a reference text. The theory used structural analysis refers to the actansial Greimas. Based on the structure of the search results found work in seven events in actant scheme that drives the plot of the novel. In this study indicates the utilization of Nyai Roro Kidul myth on the level of plot, character, and background. From the analysis of the structure of meaning found in the form of myths utilization objectification, commodification and demystified